Purification with Falcon gravity concentrator processing of low-grade bentonites and modeling. (4th May 2017) - Özgen, Selçuk
ABSTRACT: As advances in technology have led to increased use of bentonites, higher quality bentonite has been sought. The volume of high-quality bentonites available is shrinking and use of bentonite reserves containing impurities is inevitable. The aim of this study was to apply central composite rotatable design (CCRD) to model and optimize some operational parameters of a Falcon gravity concentrator (FGC) to produce bentonite concentrate. The three significant operational parameters of FGC are gravity force, solid concentration, and water pressure, and these parameters were varied and the results evaluated using the CCRD. Second-order response functions were produced for the cation exchange capacity (CEC), swelling, smectite content, and yield of smectite in the bentonite concentrates. Predicted values were calculated to be in good agreement with the experimental values ( R 2 values 0.897, 0.980, 0.948, and 0.904 for CEC, swelling, smectite, and yield of smectite of bentonite concentrations, respectively). Although in natural states this bentonite is not suitable for industrial use, purification enhanced its CEC, swelling properties, and smectite content to values of 92 meq/100 g CEC, 32 mls/2 g swelling, and 97% smectite, respectively. GRAPHICAL ABSTRACT: